Bertahan di Tengah Ketidakpastian: Habitus Guru Honorer dalam Arena Pendidikan di Kota Palopo - Mila Sari; Sumardi; Fajrul Ilmy Darussalam; Hildayanti; Ayustina Joni (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2026)
The phenomenon of honorary teachers, particularly in Indonesia, is currently a hot topic of discussion in various circles. Aspects of welfare, economics, and policy are crucial. This study aims to understand the motives of honorary teachers as a social practice for their survival in the educational arena. This study employed a qualitative approach with a case study method. Data collection techniques included observation, interviews, and documentation. The data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results indicate that honorary teachers exhibit several habitus patterns in their educational endeavors, including interpreting their profession as a calling, satisfying emotional relationships with the school environment, and hoping to build future career opportunities. Efforts to survive in the educational arena include undertaking side jobs to strengthen economic capital, participating in self-development training to enhance cultural capital, and taking on additional roles in schools to strengthen social and symbolic capital. This study demonstrates the importance of a thorough understanding of the existence of honorary teachers in the educational world. A comprehensive understanding of the social reality of honorary teachers can lead to educational policies and strategies that benefit all parties.